Burkina Faso : Requests for Disbursement Under the Rapid Credit Facility and Rephasing of Access Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2020)
This paper discusses Burkina Faso's Requests for Disbursement Under the Rapid Credit Facility (RCF) and Rephasing of Access Under the Extended Credit Facility. The immediate challenge is to contain the spread of coronavirus disease 2019, strengthen medical care, implement the social distancing and other containment measures, and mitigate the socio-economic impact of the pandemic, especially on the most vulnerable. The authorities' measures to contain and mitigate the socio-economic fallout of the pandemic have given rise to substantial and urgent fiscal and balance of payments needs. With uncertainties surrounding the duration and scope of the pandemic, the fallout could intensify further. The IMF emergency support under the RCF will provide much-needed resources to support the authorities' response to the crisis and help catalyze further donor support. A widening of the fiscal deficit in 2020 is warranted to create room for health care spending, social safety nets and for the mitigation of the economic impact of the shocks. Prioritized, well-targeted and cost-effective spending would be critical.